Film and Audiovisual Education in the Artificial Intelligence Era: Approaches and Challenges - Elisa Farinacci (Cinergie)
The integration of AI into audiovisual culture heralds a profound shift in creation, interpretation, and cultural legacy, extending human capacities in interacting with the world. This prompts a necessary reevaluation of human cultural and artistic legacies, demanding a mindful approach in Media and Audiovisual Education to address AI mechanisms, biases, and dataset selection processes. Given AI’s creative potential, not only within the audiovisual and ICT industries but also for Web 2.0 users at large, several pressing questions emerge for media and audiovisual educators and scholars. Challenges regarding integrating AI technologies, the need to reevaluate traditional educational approaches, and considerations for new methodological implementations warrant attention. This paper proposes a new model for integrating AI into media and audiovisual education: the AI Audiovisual Literacy (AIAL) framework. Through this framework, we seek to bridge our current understanding of AI with traditional educational approaches, offering a structured method for addressing the challenges and opportunities presented by AI in the realm of audiovisual media culture.